Russian Regions: Foreign Trade and Economic Development - Vladimir Sherov-Ignatyev (European Regional Science Association (ERSA), 2013)
Russia is one of the most heterogeneous countries, consisting of more than 80 regions. Among other features, its regions vary by their involvement in international trade and by vulnerability to external shocks. Russian economy is becoming more open, but openness of regions varies greatly, depending to the large extent on the endowment by natural resources. The beginning of the second decade of the century was marked by the serious breakthrough in Russia?s role in the processes of global and regional integration. Russia, Belarus and Kazakhstan arranged a functioning customs union (CU RBK), and in 2012 Russia fully joined the World trade organization. The goal of the current study is to examine the diversity of Russian regions and to assess the role of external trade in local economic development across Russia. We specially discuss the probable impact of WTO accession and CU RBK arrangement on the economic development of Russian regions. We start with the general overview of Russian regional diversity, examine commodity structure and geography of foreign trade by eight federal districts of Russian Federation and then discuss the factors influencing foreign trade patterns of specific regions. Regression analysis is used for explaining regional import per capita and for testing dependence of incomes on export and some other factors, including geographic location. . The conclusions are as follows: two capitals, Moscow and St. Petersburg, some industrial agglomerations with huge metallurgic plants and major sea ports (especially Kaliningrad) enjoy the main benefits of the WTO accession of Russia. Oil- and gas-rich regions do not expect serious effect. On the other hand, regions specialized on manufacturing and agriculture and located in the middle of the country are subject to tangible negative impacts of the WTO accession. The customs union formation gives a chance to alleviate such negative development, providing easier access to the neighbor markets thanks to trade diversion and trade creation effects of regional integration. It is important to stress the fact, that such effects emerge not thanks to tariffs elimination (free trade regime existed before the CU creation as well), but due to the elimination of the border customs control on the internal; borders of the CU RBK.
Keywords: F14; F15; F43; P25; P48; R12; 330; Russia; export; regional diversity; WTO; customs union; integration